Intermittent fasting combined with exercise training reduces body mass and alleviates hypothalamic disorders induced by high-fat diet intake - Oliveira, Luciana da Costa; Morais, Gustavo Paroschi; de Oliveira, Franciane Pereira; Mata, Milene Montavoni; Veras, Allice Santos Cruz [UNESP]; da Rocha, Alisson Luiz; Elias, Lucila Leico Kagohara; Teixeira, Giovana Rampazzo [UNESP]; de Moraes, Camila; Cintra, Dennys E.; Ropelle, Eduardo R.; de Moura, Leandro P.; et al. (Elsevier, 2023)
High-fat diet consumption causes hypothalamic inflammation, dysregulating the leptin pathway, which, in turn, compromises the modulation of hypothalamic neuronal activities and predisposes obesity development. Intermittent fasting (IF) and exercise training (ET) have been demonstrated as efficient interventions to modulate hypothalamic inflammation and neuronal activity. However, no studies have evaluated whether combining these interventions could induce better results in reestablishing hypothalamic homeostasis disrupted by high-fat diet intake. The 8-week-old male C57BL/6 mice were randomly assigned into 2 groups: sedentary mice fed a standard diet (CT), and sedentary mice fed a high-fat diet (HF). After 8 weeks of an HF diet, part of the HF group (now 16 weeks old) was randomly subjected to different interventions for 6 weeks: HF-IF = HF diet mice submitted to IF; HF-T = HF diet mice submitted to ET; HF-IFT = HF diet mice submitted to IF and ET. All interventions decreased the body weight gain induced by high-fat diet intake, associated with reduced calorie consumption in week 14. Only the HF-IFT group presented improved serum insulin, leptin, resistin, and Tnf-alpha levels concomitantly with decreased hypothalamic inflammation. The HF-IFT group also demonstrated increased Pomc mRNA expression associated with enhanced pSTAT3 expression in the hypothalamic arcuate and ventromedial hypothalamic nuclei. Our data indicate that the beneficial effects of the combination of IF and ET on energy homeostasis are associated with increased leptin sensitivity in the hypothalamic arcuate nucleus and ventromedial hypothalamic nucleus, which is likely due to an improvement in hypothalamic inflammatory pathways in these nuclei.
Keywords: Hypothalamus; Intermittent fasting; Leptin; Obesity; Physical exercise